(untitled) (Margalla Papers, 2024)
China's ascendant position in International Relations has sparked a debate over the future of the US-led liberal international order. As China's military, economic, ideological, and institutional influence continues to expand, apprehensions about its challenges to the existing global order and the evolution of China's role in international governance have intensified. This research is qualitative and consults both primary and secondary recourses. From the neo-Gramscian school of thought perspective, this research explores the core relationship between China and the global order, delving deep into the historical context. Unlike traditional international relations theories, this research presents a historical and relational interpretation to present an alternative perspective on China's rise. Elucidating this dynamic historical progression, this paper posits that China's relationship with the world order has evolved significantly, moving from animosity and refutation in the post-independence period to compliance with Western ideals and institutions, integration into the international system and, more recently, to the pursuit of independent institution-building, global governance, and promotion of alternative world order. This paper concludes that while China has adopted a predominant role in shaping the rules of the international system, it is far from being a disruptive reformist. Thus, despite its global outreach, China does not seek to build a power centre that counters explicitly the Western liberal order but signals a gradual transition towards a multipolar order. Bibliography Entry Munir, Maheera and Faiza Abid. 2024. "China, Global Governance and Liberal International Order: A Neo-Gramscian Analysis." Margalla Papers 28 (1): 93-108.